Resting muscle tension and trigger points in elite junior short-track athletes and healthy non-athletes: a cross-sectional examination - Konieczny, M.; Matuska, J.; Pakosz, P.; Domaszewski, P.; Skulska, M.; Herrero, P.; Skorupska, E. (Frontiers in Sports and Active Living, 2024)
Introduction Short-track speed skating (short track) is an Olympic sport characterized by a specific body position and counterclockwise movement on the track. Based on previous studies, we hypothesized that athlete body positions employed in this sport could lead to asymmetric overuse disorders of the left lower limb muscles. An increased number of latent trigger points (LTrPs) was confirmed in individual muscles of the overloaded left limb of short-track athletes. This study aimed to compare the number of LTrPs and the level of resting muscle tone between elite junior short-track athletes and healthy non-athletes.